FORMULASI SEDIAAN LILIN EKSTRAK MINYAK ATSIRI BUNGA SEDAP MALAM (Polianthes tuberosa ) SEBAGAI AROMATERAPI - Marbun, Nova Rianti; Br Sembiring, Tio Ranti Sari (Jurnal Penelitian Farmasi Dan Herbal, 2026)
This study aims to formulate and evaluate aromatherapy wax preparations from nightshade flower essential oil extract (Polianthes tuberosa) as an effort to handle non-pharmacological stress. The essential oil of the nightshade flower is obtained through the method of steam distillation from 10 kg of fresh flowers, resulting in 30 ml of essential oil. The characterization of simplicia showed a moisture content of 5.71%, a water soluble cider content of 17.13%, an ethanol soluble cider content of 18.01%, a total ash content of 10.82%, and an acid-insoluble ash content of 1.49%, meeting the requirements of the Indonesian Herbal Pharmacopoeia. Phytochemical screening identifies alkaloids, flavonoids, tannins, saponins, triterpenoids, and glycosides. Aromatherapy candles are formulated in four variations of essential oil concentrations (Polianthes tuberosa): 0% (F0), 5% (F1), 10% (F2), and 15% (F3), as well as one positive control (F4). Physical evaluation shows all formulas have a good, dense, and air bubble-free appearance. The hedonic test showed that the F3 formula (15% essential oil) was preferred by the panelists in terms of aroma, shape, and color, and provided a significant relaxation and refreshment effect, close to the quality of commercial products. The F3's burn time reaches 10 hours, showing good durability.